Optimization of an aircraft flight trajectory in the GLONASS dynamic accuracy field - O. N. Skrypnik; N. G. Arefyeva; R. O. Arefyev (Научный вестник МГТУ ГА, 2018)
Advanced technologies in air traffic management assume the transition to flexible routing based on the use of the satellite navigation systems. However, the accuracy of these systems depends on the location of the navigation satellites in relation to the target object and will vary in the available airspace. Therefore, the designed optimal flight path of the aircraft should be built taking into account the accuracy of its keeping in the variable navigation-time field (accuracy field) of the satellite navigation system. The accuracy field of the satellite navigation systems can be characterized by the geometric factor (spatial, horizontal and vertical). The geometric factor of the satellite navigation system is determined by the relative position of the consumer and the satellites upon which the navigation problem is solved, and is a deterministic value. Due to the orbital motion of satellites and the movement of the consumer, the geometric factor will change in space and time. Knowing the laws of the satellites orbital motion it is possible to calculate the geometric factor for any point in the air space and for any moment of time according to the known almanac of the system. This allows predicting the expected accuracy of the navigation and time determination during the flight on a particular air route. Optimization methods based on the algorithms of A-star and Dijkstra graph theory are chosen for aircraft flight trajectories construction. Mathematical modeling is used for the optimal trajectory construction in the GLONASS dynamic accuracy fields with their various structures in static and dynamic problem setting.